Comparison of: (2S,4R)-4-[18F]Fluoroglutamine, [11C]Methionine, and 2-Deoxy-2-[18F]Fluoro-D-Glucose and Two Small-Animal PET/CT Systems Imaging Rat Gliomas - Miner, Maxwell W. G.; Liljenbäck, Heidi; Virta, Jenni; Helin, Semi; Eskola, Olli; Elo, Petri; Teuho, Jarmo; Seppälä, Kerttu; Oikonen, Vesa; Yang, Guangli; Kindler-Röhrborn, Andrea; Minn, Heikki; et al. (Frontiers in Oncology, 2021)
Purpose The three positron emission tomography (PET) imaging compounds: (2S, 4R)-4-[18F]Fluoroglutamine ([18F]FGln), L-[methyl-11C]Methionine ([11C]Met), and 2-deoxy-2-[18F]fluoro-D-glucose ([18F]FDG) were investigated to contrast their ability to image orthotopic BT4C gliomas in BDIX rats. Two separate small animal imaging systems were compared for their tumor detection potential. Dynamic acquisition of [18F]FGln was evaluated with multiple pharmacokinetic models for future quantitative comparison. Procedures Up to four imaging studies were performed on each orthotopically grafted BT4C glioma-bearing BDIX rat subject (n = 16) on four consecutive days. First, a Dotarem® contrast enhanced MRI followed by attenuation correction CT and dynamic PET imaging with each radiopharmaceutical (20 min [11C]Met, 60 min [18F]FDG, and 60 min [18F]FGln with either the Molecubes PET/CT (n = 5) or Inveon PET/CT cameras (n = 11). Ex vivo brain autoradiography was completed for each radiopharmaceutical and [18F]FGln pharmacokinetics were studied by injecting 40 MBq into healthy BDIX rats (n = 10) and collecting blood samples between 5 and 60 min. Erythrocyte uptake, plasma protein binding and plasma parent-fraction were combined to estimate the total blood bioavailability of [18F]FGln over time. The corrected PET-image blood data was then applied to multiple pharmacokinetic models. Results Average BT4C tumor-to-healthy brain tissue uptake ratios (TBR) for PET images reached maxima of: [18F]FGln TBR: 1.99 ± 0.19 (n = 13), [18F]FDG TBR: 1.41 ± 0.11 (n = 6), and [11C]Met TBR: 1.08 ± 0.08, (n = 12) for the dynamic PET images. Pharmacokinetic modeling in dynamic [18F]FGln studies suggested both reversible and irreversible uptake play a similar role. Imaging with Inveon and Molecubes yielded similar end-result ratios with insignificant differences (p > 0.25) Conclusions In orthotopic BT4C gliomas, [18F]FGln may offer improved imaging versus [11C]Met and [18F]FDG. No significant difference in normalized end-result data was found between the Inveon and Molecubes camera systems. Kinetic modelling of [18F]FGln uptake suggests that both reversible and irreversible uptake play an important role in BDIX rat pharmacokinetics.